Malaysian kitchen : explore the exquisite food and cooking of Malaysia, with 80 superb recipes shown step-by-step in more than 350 beautiful photographs - Tan, Terry (Southwater, 2010)
Malaysia is a region that has many distinct localized cooking styles which is reflected in the exciting food that can be enjoyed throughout the country. This title features 80 recipes that capture the fiery and sweet flavours of this region, and includes soups, snacks, rice and noodles, fish and shellfish, meat and poultry, salads and sweets